The green adaptive reuse of historic buildings / Kartina Alauddin, Mohd Fisal Ishak and Noorzalifah Mohamed - Kartina, Alauddin; MohdFisal, Ishak; Noorzalifah, Mohamed (2015)
The green concept of adaptive reuse could become the ideal strategyas it combines embodiedand operational benefits, reduces greenhouse gas emissions and carbon footprints. However, lack of knowledge, expertise and multi-skills design and project team in understanding the green concept in adaptive reuse projects are the main problems in the application of green concept. The green concept requires technical expertise in environmental modeling, comfort and energy performance, while adaptive reuse requires the engagement and understanding of historical connections and cultural sensitivities. It is crucial to well integrate green and adaptive reuse concept because these could produce extraordinary outcomes. The purpose of this study is to propose the conceptual framework of green concept in adaptive reuse projects. Therefore, this paper discussesthe literature related to the green concept in adaptive reuse. The conceptual result in this regard would help adaptive reuse practitioners to seek out and pursue the green concept in adaptive reuse.